Safety and efficacy of a feed additive consisting of semi‐refined carrageenan for cats and dogs (Gel Systems Ltd.) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Birgit Dusemund; Mojca Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2023)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of semi‐refined carrageenan as a feed additive for cats and dogs. The EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) concluded that semi‐refined carrageenan was safe for dogs at 6,000 mg/kg final wet feed (with about 20% dry matter). This would correspond to 26,400 mg semi‐refined carrageenan/kg complete feed (with 88% dry matter). In the absence of specific data, the maximum concentration of the additive considered safe for cats was 750 mg semi‐refined carrageenan/kg final wet feed, corresponding to 3,300 mg semi‐refined carrageenan/kg complete feed (with 88% dry matter). In the absence of data, the FEEDAP Panel was not in the position to conclude on the safety of carrageenan for the user. The additive under assessment is intended to be used in dogs and cats only. No environmental risk assessment was considered necessary for such use. The FEEDAP Panel was not in the position to conclude on the efficacy of semi‐refined carrageenan as a gelling agent, thickener and stabiliser in feed for cats and dogs at the proposed conditions of use.